Diseño de una planta para la producción de tableros aglomerados a partir de residuos de envases de tetra pak en la provincia de trujillo. - Espinoza Cerrepe, Cristóbal Gonzaga (2015)
The purpose of this research is to design an industrial plant for production of chipboard of tectán in the province of Trujillo. To achieve the proposed aims, we have used the methodology of development and evaluation of investment projects as a frame of reference. This report focuses on topics such as market study, technical study, economic study, economic evaluation, and environmental assessment of the project. Thinking about the problems of solid waste management in our country, it has designed an industrial plant for recycling of carton packages from Tetra Pak. The amounts of raw material available were evaluated by analyzing reports of solid waste characterization. The plant is able to produce by physical processes about 92 chipboards a day. It will be located in the district of “La Esperanza” covering an area of 1,800 m2. Conveniently it has been distributed into administrative offices, processing area, maintenance area, sanitation, security booth, parking, loading area and expansion area. The initial investment and total operating costs were determined and the economic feasibility of the projected plant was evaluated, concluding that the design is economically feasible with an IRR of 33%. Additionally, the most significant environmental aspects of the production process were identified and control actions were proposed.